IMPLEMENTATION OF CHARACTER EDUCATION PROGRAM IN VOCATIONAL SCHOOL, LEBONG DISTRICT - Sumarsih, Sumarsih; Zakaria, Zakaria (International Journal of Educational Management and Innovation, 2020)
The purpose of the research is to describe the implementation of strengthening character education at the Vocational High School in Bengkulu. This research is a quantitative descriptive study. The study population was 156 students, and the study sample used a random sampling sample of 75 students. Data collection techniques using a questionnaire. Data analysis techniques using percentage analysis. The results showed the application of strengthening of character educationÂ  Vocational High Schools in Bengkulu; in general, the level has implemented with functional categories with a level of accomplishment reaching 75.4%. Specifically, the religious character value is good (78%), the nationalist is good (74%), independent is good (72%), cooperation is good (77%), and integrity is good (76%). It means that the strengthening of character education consists of religious, nationalist, independent, cooperation, and integrity values carried out by teachers and students according to school programs